LIBERTY INNOVATION (INFORMATION TECHNOLOGY-BASED LITERACY) AS A SCHOOL LEARNING TOOL AT STATE MIDDLE SCHOOL 2 CISAUK, TANGGERANG REGENCY - Rosidah (Jurnal Studi Inovasi, 2023)
This research is about a digital innovation called LIBERTI (Information Technology-Based Literacy) as a school learning tool at SMP Negeri 2 Cisauk. This study was conducted by the Regional Government of Tangerang Regency. This research is important and relevant because it looks at the condition of students at SMP N 2 Cisauk, Tangerang Regency. In addition, this research is a form of local government efforts in improving the quality of education in the era of the Industrial revolution 4.0. It is hoped that it will facilitate the way educators teach and learn how to learn. The population in this study are regions that have implemented policies or innovations in the digital and education fields. While the sample in this study is the innovation "LIBERTI" (Information Technology-Based Literacy). The results of the activities that have been implemented from the utilization of LIBERTI literacy include: every day in all subject hours can be effective, change the mindset of students to be more independent in learning, solve problem solving in learning models and limitations in appropriate use, provide experience about resources good technology together with mentoring, looking for scientific information according to the subject visually and non-visually, providing good habits to use social media appropriately and according to needs as well as being a repository of accurate scientific information.